F Factors Driving Sound System Culture on Economic Growth by the Sukorambi Community, Jember Regency: Faktor Pendorong Budaya Sound System Pada Pertumbuhan Ekonomi Oleh Masyarakat Sukorambi Kabupaten Jember - Riska Fitriyah (Econetica: Jurnal Sosial, Ekonomi, dan Bisnis, 2025)
This research was conducted to find out how the space for community participation was built by sound lovers in the Sound Miniature Contest in Sukorambi Village. The emergence of this community is based on the same perception and goal, namely that both are fond of sound systems. This research method is qualitative and uses an ethnographic approach. Retrieval of data using observation techniques, interviews, and documentation. The data obtained were analyzed with the theory of postmodernism. The result of this research is that the community of sound system lovers has changed the pattern of interaction among people who share the same passion for forming unique traditions. which, in the end, can provide impetus to improve the economic system of the people of Sukorambi Village through the unique traditions that youth create.